Analytic study of hormone receptor status of breast cancer patients visiting in a tertiary care hospital of North-West India - Kakkar, Vikas; Kaushal, Arvind; Hanspal, Swaraj; Singh, Karanvir; Randhawa, Anmol; Kaur, Harpreet (International Surgery Journal, 2021)
Background: Increasing evidence shows the importance of young age, estrogen receptor (ER), progesterone receptor (PR) status, and HER-2 expression in patients with breast cancers. Breast tumors in younger age groups were more likely to be of higher grade, hormone receptor– negative, poorly differentiated, and aneuploid, and to have high S-phase fraction, abnormal expression of P53, greater extent of lymphovascular invasion, and over-expression of human epidermal growth factor receptor 2 (HER-2) than breast tumors in older age groups. Methods: We organised a retrospective study of 600 women diagnosed with breast cancer, who have been operated from 2016 to 2020. We evaluated age, size, hormone receptor status, HER-2 receptor status. Estrogen receptor and progesterone receptor status were evaluated by immunohistochemistry. Results: Total 600 patient data was evaluated in this study. Rate of hormone positivity is more in older patients than in younger patients. Conclusions: In this study we conclude that the hormone positivity in younger patient is less as compared to older patients.